Drivers for Renewable Energy Consumption in European Union Countries. A Panel Data Insight - Iulia Lupu; Gheorghe Hurduzeu; Radu Lupu; Maria-Floriana Popescu; Camelia Gavrilescu (Amfiteatru Economic, 2023)
Renewable energy sources play an essential role in the broader context of environmental protection and the fight against the effects of climate change. At the European level, the need to increase the proportion of energy generated by renewable resources is formalised through the Renewable Energy Directive (2009/28/EC), which was updated in 2018 and became legally mandatory starting from June 2021. The European Green Deal, adopted in 2019, highlights the role of energy generated from renewable sources in fulfilling more complex objectives recognised at the international level. Within this context, in this study, we investigate the link between renewable energy consumption by sector and other critical indicators in the energy sector, representing energy productivity, intensity, efficiency, import dependency, research and development (R&D) allocations, and energy-related tax revenues, for the period 2004-2020. We employed a panel data approach for European Union member states, Central and Eastern Europe and Western Europe countries separately. The empirical results confirm the different conditions for the two groups of countries, suggesting the possibility of designing specific energy policies. We emphasise the positive role of R&D in both categories of member states.
Keywords: Q20; C23; Q40; R58; 330; renewable energy; energy policy; European Union; panel data.